The development of a tablet-based outpatient care for people with dementia – A feasibility study (Preprint) - Juliana Supplieth; Sonia Lech; Julie L. O’Sullivan; Robert Spang; Jan‐Niklas Voigt-Antons; Johanna Schuster (2024)
BACKGROUND Dementia presents a significant challenge for individuals affected by it, as well as their families, caregivers, and healthcare providers. OBJECTIVE This paper outlines the process of developing and assessing the feasibility of a tablet application aimed at addressing this challenge. It underscores the importance of incorporating input from general practitioners, stakeholders, and the needs of affected families to create a supportive healthcare app. METHODS A qualitative approach was chosen, consisting of three interviews and an expert workshop. Both were recorded, transcribed and the qualitative content analysis was carried out according to the methodology described by Kuckartz with the support of MAXQDA. During the development phases of the app, team meetings and discussions took place bi-weekly. RESULTS This paper emphasizes the necessity of considering multiple perspectives to ensure the high-quality development of supportive healthcare apps. General practitioners and relatives play pivotal roles in the treatment and care of Persons with Dementia, often expressing specific preferences and suggestions regarding supportive assistive technologies. Moreover, successful development of a useful tablet application requires robust scientific, multidisciplinary discussions, and teamwork within the healthcare community. CONCLUSIONS The collaboration among medical disciplines, social and technical sciences, as well as supporting organizations is essential to integrate relevant knowledge and expertise into the design and development of practical products tailored to the daily needs for healthcare of end users. Furthermore, adopting a spiral development approach inclusive of feedback loops is imperative for iterative refinement and enhancement of the application. CLINICALTRIAL ISRCTN 36542 INTERNATIONAL REGISTERED REPORT RR2-10.1024/1662-9647/a000210